Chromosomal DNA damage in APOE ɛ4 carriers and noncarriers does not appear to be different. (25th March 2015) - Chua, Ann; Thomas, Philip; Clifton, Peter; Fenech, Michael
<x xml:space="preserve">Abstract</x> DNA damage may play a key role in promoting disease‐onset and accelerated disease progression in Alzheimer's disease (AD) by increasing the rates of neuronal cell death. The ɛ4 allele of the APOE gene is the best characterised genetic risk factor for AD, however, it is unknown if APOE ɛ4 carriers exhibit increased levels of DNA damage which may contribute to increased AD risk. 175 healthy participants (aged 34–67 years old) from South Australia were recruited into the study and provided a single blood sample for the isolation of peripheral blood lymphocytes, APOE genotyping and lymphocyte chromosomal DNA damage analysis using the Cytokinesis‐Block micronucleus cytome (CBMN‐Cyt) assay with the micronucleus index being the primary outcome measure. When compared to non‐APOE ɛ4 carriers, APOE ɛ4 carriers did not exhibit altered rates of i) cell division, represented by the nuclear division index (NDI, P = 0.372), ii) cell death as represented by apoptotic (P = 0.457) and necrotic (P = 0.393) frequencies and iii) chromosomal DNA damage as indicated by the number of micronuclei (MNi, P = 0.795), nucleoplasmic bridges (NPBs, P = 0.221) or nuclear buds (NBUDs, P = 0.293) scored in binucleated cells. In conclusion, although we and others have previously shown that rates of chromosomal DNA damage measured using the CBMN‐Cyt assay are elevated in individuals with cognitive impairment, in this South Australian cohort the frequency of genome instability is not substantially influenced by the presence of the APOE ɛ4 allele. Environ. Mol. Mutagen. 56:694–708, 2015. © 2015 Wiley Periodicals, Inc.